Ethical Leadership and Subordinate Outcomes: The Mediating Role of Organizational Politics and the Moderating Role of Political Skill - Kacmar, K. Michele; Andrews, Martha C.; Harris, Kenneth J.; Tepper, Bennett J. (2013)
This paper posits that ethical leadership increases important organizational and individual outcomes by reducing politics in the workplace. Specifically, we propose that perceptions of organizational politics serve as a mechanism through which ethical leadership affects outcomes. We further argue that the modeled relationships are moderated by political skill. By means of data from 136 matched pairs of supervisors and subordinates employed by a state agency in the southern US, we found support for our predictions. Specifically, we found that perceptions of organizational politics fully mediated the relationship between perceptions of ethical leadership and helping and promotability ratings. In addition, political skill was found to moderate the direct and indirect effects.
Keywords: Promotability ratings; Helping; Organizational Politics; Political skill; Ethical Leadership